Artifacts affecting dual-energy X-ray absorptiometry and bone mineral density measurements: a case report and review of the literature - Kevin White; Mohamed K. M. Shakir; Christopher Nguyen; Thanh D. Hoang (Journal of Medical Case Reports)
Abstract Introduction It is important to recognize artifacts of dual-energy X-ray absorptiometry because they may alter bone mineral density measurements. To prevent erroneous decisions and misdiagnosis regarding treatment and follow-up, bone mineral density measurement adjustments are needed. Case presentation We present three cases in which artifacts altered the measurements of bone mineral density in the lumbar field of a dual-energy X-ray absorptiometry scan. The first case was oral contrast in the transverse colon in a 55-year-old white Hispanic American woman; the second case was kyphoplasty in lumbar spine in a 73-year-old white Hispanic American woman; and the third case was spinal fusion with vertebroplasty in a 70-year-old white European American man. Conclusion Clinicians who interpret dual-energy X-ray absorptiometry imaging should routinely reexamine the scans and be attentive toward potential artifact involvement and other alternative origins of unreliable data.